Dual Relationships Between Transformational Leadership Perceptions and Organizational Commitment: A Preliminary Research - Ayranci, Evren (European Scientific Journal, ESJ, 2017)
Business environment has always been addressed by various scientific studies via many subjects, theories, and paradigms. While some of these have been very popular in the literature, some have not attained much concern. This study emphasizes two of the very prominent subjects, namely transformational leadership and organizational commitment. What are characteristic to this study are that the existence of top managers’ leadership feature (if any) are interpreted by the workers; workers express the extent to which they perceive their top managers as transformational leaders; and workers’ organizational commitment is investigated to unearth any potential relationships with this transformational leadership perception. These relationships are expected to be reciprocal. In other words, it is expected that workers’ organizational commitment affects and is affected by how much they perceive their top managers as transformational leaders. This expectation is tested in İstanbul Tuzla Organized Industrial Zone by a model proposed with the intentions of finding related facts about Turkish businesses, and reaching some implications about connections between transformational leadership’s nature and organizational commitment. The main result acknowledges this expectation: there is a positive and moderate reciprocal connection.